2016 38th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2016
DOI: 10.1109/embc.2016.7591760
|View full text |Cite
|
Sign up to set email alerts
|

Corticomuscular coherence variation throughout the gait cycle during overground walking and ramp ascent: A preliminary investigation

Abstract: Recent designs of neural-machine interfaces (NMIs) incorporating electroencephalography (EEG) or electromyography (EMG) have been used in lower limb assistive devices. While the results of previous studies have shown promise, a NMI which takes advantage of early movement-related EEG activity preceding movement onset, as well as the improved signal-to-noise ratio of EMG, could prove to be more accurate and responsive than current NMI designs based solely on EEG or EMG. Previous studies have demonstrated that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Coherence increased significantly in the beta and gamma bands in relation to visually guided walking without any changes in the alpha band. Previous findings have suggested that intra-and intermuscular coherence in the beta and gamma bands during walking is related to corticospinal activity, since coherence at similar frequencies are 1) observed for paired EEG and EMG recordings (Petersen et al 2012;Storzer et al 2016;Winslow et al 2016), 2) greatly reduced following lesion of the corticospinal tract (Hansen et al 2005;Nielsen et al 2008;Barthelemy et al 2010;Petersen et al 2013) and 3) increased in relation to maturation of the corticospinal tract (Farmer et al 2007;James et al 2008;Petersen et al 2010). In line with this, corticomuscular coherence in the beta and gamma frequency bands also increased during visually guided walking although it did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coherence increased significantly in the beta and gamma bands in relation to visually guided walking without any changes in the alpha band. Previous findings have suggested that intra-and intermuscular coherence in the beta and gamma bands during walking is related to corticospinal activity, since coherence at similar frequencies are 1) observed for paired EEG and EMG recordings (Petersen et al 2012;Storzer et al 2016;Winslow et al 2016), 2) greatly reduced following lesion of the corticospinal tract (Hansen et al 2005;Nielsen et al 2008;Barthelemy et al 2010;Petersen et al 2013) and 3) increased in relation to maturation of the corticospinal tract (Farmer et al 2007;James et al 2008;Petersen et al 2010). In line with this, corticomuscular coherence in the beta and gamma frequency bands also increased during visually guided walking although it did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…; Winslow et al. ), 2) greatly reduced following lesion of the corticospinal tract (Hansen et al. ; Nielsen et al.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic investigation of CMC at different walking speeds may help to resolve the timing of intra-stride modulations of CMC, as the activations patterns of the TA muscle are strongly modulated by walking speed (den Otter et al 2004). The case-reports by Winslow et al (2016) and Brantley et al (2016) investigated CMC during overground walking in a single subject over a single gait cycle: Winslow et al (2016) observed CMC between motor cortex and TA at approximately 18-23 Hz just after heel strike and just after toe-off, whereas Brantley et al (2016) reported CMC between motor cortex and TA at frequencies below 5 Hz throughout the gait cycle. Artoni and colleagues (2017) recently showed a descending connectivity from motor cortical regions to different leg muscles during the swing phase of steady-state treadmill walking.…”
Section: Discussionmentioning
confidence: 99%
“…High beta CMC was significantly enhanced during overground walking compared to treadmill walking. To our knowledge, no previous study has compared corticospinal dynamics between locomotor tasks, but only investigated it during treadmill walking (Artoni et al 2017; Petersen et al 2012; Winslow et al 2016). However, a number of studies have assessed cortical oscillations during various gait tasks and have found task-dependent differences in cortical beta power (Bruijn et al 2015; Bulea et al 2015; Knaepen et al 2015; Lisi and Morimoto 2015; Oliveira et al 2017b; Sipp et al 2013; Wagner et al 2016; Wagner et al 2012; Wagner et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation